Estimación del potencial remediador de metales en plantas vasculares herbáceas en el “Cerro El Toro” Shiracmaca – Huamachuco, Perú. 2016 - Alarcon Rojas, Narda Marisol (2019)
ABSTRACT In the hill "El Toro" (La Libertad region), where intense informal mining activity takes place, with negative impacts on the environment, it was proposed to determine the plants with phytoremediation potential. Four working points were considered, where samples of superficial soil were taken and the present herbaceous vascular plants were collected. The material was transferred to the Botanical Laboratory of the Faculty of Biological Sciences of the National University of Trujillo, for the determination of species and preparation of soil and plant samples for analysis; the determination of metals was done through an ICP-OES. The results have evidenced that there is a high content of heavy metals in the soil, especially As, Ba, Mn, Pb and Zn, surpassing the national and international revised norms; likewise, it has been demostrated that Bidens triplinervia behaves like a phytostabilizing plant of Pb and Zn, whereas Lepidium pubescens and Nasturtium officinale are hyperaccumulators of Pb that efficiently transfer the Zn from the root to its aerial organs.